ELICITATION TECHNIQUES USED BY A PRE-SERVICE TEACHER IN EFL CLASSROOM - Kamilah, Firdha Akhdania; Cahyani, Lilis Indah (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2020)
English as a foreign language only practiced in particular occasions and one of them is in classroom. It means classroom is a place where EFL learners mainly improve their English abilities. However, EFL learners tend to be passive learners because they are afraid of making mistakes and getting negative feedback from teacher. It leads EFL classroom has less interaction which affect EFL learners’ achievement. In order to enhance classroom interaction, teacher could use kinds of elicitation techniques. This study aims to find kinds of elicitation techniques used by a pre-service teacher in EFL classroom by using categorization from Long and Sato (1983) and Richards and Lockhart (1996). Besides, it is also to find its dominant kind. This study used qualitative research method and the data were gathered form transcript of a teaching video. Other than that, the data were analyzed qualitatively. The result showed that based on Long and Sato's (1983) categorization, 62 display questions (80.52 %) and 15 referential questions (19.48 %) found in EFL classroom. In addition, based on Richards and Lockhart’s (1996) categorization, 15 procedural questions (19.48 %), 55 convergent questions (71.43 %), and 7 divergent questions (9.09 %) found in EFL classroom. Furthermore, based on the nature of interaction, the dominant kind of elicitation technique was display question (80.52 %) while based on its purpose; convergent question (71.43 %) dominantly used by a pre-service teacher in EFL classroom.Key words: Elicitation techniques, Pre-service teacher, EFL learners, EFL classroom.